Anthropometry as Indicator of the Family Economic Condition - Lely Wahyuniar; Bambang Sutrisna; Abas B. Djauhari; Ratna Djuwita (Media Kesehatan Masyarakat Indonesia, 2020)
The prevalence of Indonesian population experiencing hunger reaches 20.1%.Anthropometry is considered capable to measure socio-economic conditionsbecause it is directly related to the financial purchasing power of food that affectsintake patterns. The aim of this study is to test the reliability of the familyanthropometry using Height for Age Z Score (HAZ) index and Body Mass Index ZScore (BMIZ) as indicator of the family economic condition. This cross-sectionalstudy design located in Astanajapura (Rural) and Kesambi (Urban) Subdistrict,Cirebon, West Java. The stratification sampling method was held to obtainsamples from all main family members of the selected households (1,999persons) from 405 families. Data analysis used ROC method to obtain the cut-offpoints of anthropometry index, validity test for sensitivity and specificity, andKappa test for the reliability test. The findings indicate that the family HAZanthropometry index could represent the family economic condition better thanthe BMIZ and it is reliable to become an indicator for the economic condition bothin rural and urban areas. There is a positive correlation between consumption percapita and the HAZ index where the higher the family HAZ z score is, the higherthe family consumption per capita. The method can be used to measure the poorprevalence in macro level and select the target of poor families in the micro levelusing the family HAZ anthropometry index. It is recommended to use HAZ indexto estimate prevalence of poor families within the micro level, but the processmust not include children under two years old due to the technical obstacleduring measurement and other substance factors. Further research is needed toproduce a more accurate method in using the family anthropometry as anindicator of family economic condition.